DUNBROCH ROYAL FAMILY CHARACTERS AND THEIR ROLE IN BRAVE FILM (2012) - Carolina, Armelia; Natsir, M.; Lubis, Indah Sari (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
The aim of this research is to find out the characters of the Dunbroch Royal Family members which consists of Merida, Queen Elinor, King Fergus, Harris, Hubert and Hamish  as well as their role in the plot of the Brave (2009) film. There are two data sources in this research. First is the Brave (2009) film, and the second is the script of this film itself. The data then categorized by using Reams’s characterization. The role of the characters the connected wirh Kenney’s plot development. The result of this research show that Dunbroch Royal Family member characters consist of four different kind of characters and all of them except for King Fergus have a significant role in the plot of the story.